The model of software execution time remote testing - Chopey, Ratybor; Knysh, Bohdan; Fedasyuk, Dmytro (Видавництво Львівської політехніки, 2017)
The work deals with the problems of testing embedded systems in the case when the latter are geographically distributed, which is gradually getting more common. The analysis of the application domain has revealed the lack of information concerning remote testing of the execution time of an embedded system. The authors have investigated into the possibility of evaluating the duration of time-critical functions of a distant embedded system. We’ve introduced a model and an algorithm for measuring the firmware execution time remotely that sustained approbation with a number of experiments.
Keywords: execution time testing; worst-case execution time; embedded system; Keil uVision; UVSOCK